2012
DOI: 10.1159/000339821
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Growth Hormone Affects the Density and Functionality of GABA<sub>B</sub> Receptors in the Male Rat Brain

Abstract: The beneficial effects of growth hormone (GH) on memory and learning have previously been confirmed in both humans and in animal models. An important role of GABAB receptors for multiple forms of learning and memory has also been reported. In this study, we examined the effect of GH on the density and functionality of the metabotropic GABAB receptors in the rat brain. Male Sprague-Dawley rats (n = 24) divided into 3 groups were injected twice daily with recombinant human GH (0.07 or 0.7 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…An additional clinical trial of the same group carried out on 30 adults (age 55–87 years, 17 with MCI), using the same GHRH analog at the same doses and time, showed that this treatment significantly increased gamma-aminobutyric levels acid (GABA) in three brain regions of the left side (frontal dorsolateral, posterior cingulate, and posterior parietal), increased N -acetylaspartylglutamate in the frontal cortex, and decreased myoinositol (an osmolyte related to AD) in the posterior cingulate, inducing a positive effect on cognition in both groups of participants without affecting the regulation of plasma glucose [73]. However, in that study, no changes were found in brain glutamate levels, unlike what has been reported in preparations of hippocampal cuts from old rats treated with GH or IGF-I [32], but consistent with the effects of GH on the density and functionality of GABAB receptors in male rats in areas of the brain related to cognition [74]. These data seem to support our findings using GH in this study because although it cannot be discarded that GHRH exerts its own effects at the brain level, as it seems to do in other territories, it is clear that the administration of GHRH or one of its analogues induces the release of GH [75].…”
Section: Discussionsupporting
confidence: 71%
“…An additional clinical trial of the same group carried out on 30 adults (age 55–87 years, 17 with MCI), using the same GHRH analog at the same doses and time, showed that this treatment significantly increased gamma-aminobutyric levels acid (GABA) in three brain regions of the left side (frontal dorsolateral, posterior cingulate, and posterior parietal), increased N -acetylaspartylglutamate in the frontal cortex, and decreased myoinositol (an osmolyte related to AD) in the posterior cingulate, inducing a positive effect on cognition in both groups of participants without affecting the regulation of plasma glucose [73]. However, in that study, no changes were found in brain glutamate levels, unlike what has been reported in preparations of hippocampal cuts from old rats treated with GH or IGF-I [32], but consistent with the effects of GH on the density and functionality of GABAB receptors in male rats in areas of the brain related to cognition [74]. These data seem to support our findings using GH in this study because although it cannot be discarded that GHRH exerts its own effects at the brain level, as it seems to do in other territories, it is clear that the administration of GHRH or one of its analogues induces the release of GH [75].…”
Section: Discussionsupporting
confidence: 71%
“…Finally, metabotropic glutamate receptors (mGluRs) can modulate synaptic transmission in the ACC 34 . As elsewhere in the cortex, GABA is the major inhibitory transmitter in the ACC, where it acts on both type A GABA (GABA A ) receptors 35 and GABA B receptors 36,37 . Activation of GluK1-containing kainate receptors in the ACC can regulate GABA release 35 .…”
Section: Trace Fear Conditioningmentioning
confidence: 99%
“…GABA B receptor has been reported to be important for neuronal excitability and plasticity and is suggested to be involved in the regulation of long-term potentiation, which is the cellular mechanism for learning and memory 15,20) . GH treatment affects the functionality and density of GABA B receptors in the area of the brain associated with cognition 16) . Other studies have revealed that GH treatment up-regulated the expression of GABA BR1 transcript in rat brain, suggesting a connection between GH and the GABA B system 17,21) .…”
Section: Discussionmentioning
confidence: 99%
“…The functional GABA B receptors consist of two subunits, GABA BR1 and GABA BR2 13) , which are responsible for the neuromodulatory effect of GABA 14,15) . Recently, exogenous GH has been reported to increase the abundance of the GABA B receptor in rat brain 16) and GABA BR1 gene expression in hypophysectomised rat 17) . These findings suggest a possible correlation between GH-induced cognitive function and the GABA B receptor.…”
Section: Introductionmentioning
confidence: 99%